Hundertwasser's theory and its relation to the Slow fashion movement (ModaPalavra e-periódico, 2020)
This article proposes to develop a relationship between behavioral tendencies, the work of Hundertwasser’s artist and the Slow fashion movement, and understand better how fashion influences personal attitudes and how it has contributed to huge changes of the current market. Demonstrate through the behavioral analysis that each identity is built from the consumes and way of life.
Keywords: fashion design; trend; hundertwasser